The Factors Influencing The Purchase of Ornamental Plants (Case Study of Monstera and Philodendron Products) - Noorisiva Larasati; Ujang Sumarwan; Popong Nurhayati (School of Business, IPB University (SB-IPB), 2024)
Ornamental plants contributed greatly to the economy and could be a profitable business opportunity. The trend of ornamental plants in Indonesia was never empty; every year, there were always booming ornamental plants. The purpose of this study was to explain how the consumption behavior patterns of leaf ornamental plant products and the factors that influenced purchases included motivation, lifestyle, and marketing mix through perception as an intervening variable. This study used SEM-PLS analysis of 214 respondents who had purchased Monstera and Philodendron with a minimum age of 19 years. The results of the study showed that motivation, lifestyle, and conversation had a significant effect on perception. Motivation, co-creation, currency, communal activation, and perceptions directly influenced the purchase of leaf ornamental plants. Then, motivation had a significant effect on purchasing leaf ornamental plants indirectly, namely through perception as an intervening variable. Managerial implications in this research were segmentation, targeting, and positioning (STP) strategies and optimizing the variables that influenced the purchase of leaf ornamental plants, which consisted of motivation, co-creation, currency, communal activation, and perception. Keywords: ornamental plants, lifestyle, marketing mix, monstera, philodendron